Phylogenetic Revision of the Genus Aliivibrio: Intra- and Inter-Species Variance Among Clusters Suggest a Wider Diversity of Species - Klemetsen, Terje; Karlsen, Christian R.; Willassen, Nils P. (Frontiers in Microbiology, 2021)
Genus Aliivibrio is known to harbor species exhibiting bioluminescence as well as pathogenic behavior affecting the fish farming industry. Current phylogenetic understanding of Aliivibrio has largely remained dormant after reclassification disentangled it from the Vibrio genus in 2007. There is growing evidence of wider diversity, but until now the lack of genomes and selective use of type strains has limited the ability to compare and classify strains firmly. In this study, a total of 143 bacterial strains, including 51 novel sequenced strains, were used to strengthen phylogenetic relationships in Aliivibrio by exploring intra-species and inter-species relations. Multilocus sequence analysis (MLSA), applying the six housekeeping genes 16S rRNA, gapA, gyrB, pyrH, recA and rpoA, inferred 12 clades and a singular branch in Aliivibrio. Along with four new phylogenetic clades the MLSA resolved prior inconsistencies circumscribing Aliivibrio wodanis and formed a unique clade we propose as the novel species Aliivibrio sp. "friggae". Furthermore, phylogenetic assessment of individual marker genes showed gyrB, pyrH and recA superior to the 16S rRNA gene, resolving accurately for most species clades in Aliivibrio. In this study we provide a robust phylogenetic groundwork for Aliivibrio as a reference point to classification of species.